Iranian men's attendance in pregnancy - Arezo Aliabedian; Mouloud Agajani Delavar; Arsalan Khan Mohammmadi (Babol University of Medical Sciences, 2015)
Introduction: The benefits of male involvement in pregnancy have recently gained recognition. The aim of this study was to explore the prevalence of Iranian men's attendance during pregnancy and its association with socio-demographic factors in Babol, Iran. This study also aimed to improve the male involvement in maternal health in Iran. Methods: In a cross sectional study, a total number of 600 pregnant women, attending the antenatal clinics in both public and private medical centers from Feb. to Sep. 2015, were selected through a systematic random sampling method. A semi-structured questionnaire comprising 10-item, two-choice questions (Yes-No) elicited information about the men's attendance at antenatal clinic, their help with household chores, their attendance at counseling sessions, and their paying for the pregnancy service bills. Results: According to the results, 414 husbands under study (69.0%) accompanied their wives to the antenatal clinic during the pregnancy. Nearly, less than half of the husbands (42.5%) helped their wives with household chores during pregnancy. After adjusting for suspected confounding factors, the OR of Iranian men's attendance at antenatal clinic for men with special job was  2.76 (95% CI, 1.26 - 6. 05 P = 0.011), and for men with low educational level, it was 0.404 (95% CI, 0.18 - 0.90 P = 0.026). In addition, the OR of Iranian men's at household chores for men with special job was 2.60 (95% CI, 1.43 - 4. 74 P = 0.002), and for men with educational level between 7 to 12 years, it was 0.404 (95% CI, 0.18 - 0.90 P = 0.002). No significant associations were found between Iranian men's attendance in pregnancy with the age of men and women, income, residence status, education of women, job of women, birth order, or pregnancy intention. Conclusion: The findings of this study indicated that the Iranian men's attendance in pregnancy is low. The Iranian Ministry of Health should strive to provide adequate guidelines for the development of male involvement in pregnancy.